Astragaloside-IV protects H9C2(2-1) cardiomyocytes from high glucose-induced injury via miR-34a-mediated autophagy pathway - Yaobin Zhu; Xin Qian; Jingjing Li; Xing Lin; Jiewei Luo; Jianbin Huang; Zhao Jin (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Diabetic cardiomyopathy (DCM) is an important cardiac disorder in patients with diabetes. High glucose (HG) levels lead to inflammation of cardiomyocytes, oxidative stress, and long-term activation of autophagy, resulting in myocardial fibrosis and remodelling. Astragaloside-IV (AS-IV) has a wide range of pharmacological effects. This study aimed to investigate the effects of AS-IV on injury induced by HG in rat cardiomyocytes (H9C2(2-1)) and the involvement of the miR-34a-mediated autophagy pathway. An AS-IV concentration of 100 μM was selected based on H9C2(2-1) cell viability using the cell counting kit-8 (CCK-8). We found that 33 mM HG induced a morphologic change in cells and caused excessive oxidative stress, whereas AS-IV inhibited lipid peroxidation and increased superoxide dismutase activity. In terms of mRNA expression, HG increased miR-34a and inhibited Bcl2 and Sirt1, whereas AS-IV and miR-34a-inhibitor reversed the above effects. Further, LC3-GFP adenovirus infection and western blotting showed that HG increased autophagy, which was reversed synergistically by AS-IV and miR-34a-inhibitor. Bcl2 and pAKT/AKT protein expressions in the HG group was significantly lower than that in controls, but AS-IV and miR-34a-inhibitor antagonized the process. Thus, AS-IV inhibits HG-induced oxidative stress and autophagy and protects cardiomyocytes from injury via the miR-34a/Bcl2/(LC3II/LC3I) and pAKT/Bcl2/(LC3II/LC3I) pathways.